Hierarchical phase evolution in a lamellar Al0.7CoCrFeNi high entropy alloy involving competing metastable and stable phases. (November 2021) - Srimark, K.; Dasari, S.; Sharma, A.; Wangyao, P.; Gwalani, B.; Rojhirunsakool, T.; Gorsse, S.; Banerjee, R.
Abstract: Guided by solution thermodynamic modeling coupled with detailed experimental characterization, the present study establishes that the alternating FCC and BCC lamellar microstructure in the Al0.7 CoCrFeNi high entropy alloy, is a result of non-equilibrium partitionless solidification from the liquid to single B2 phase, followed by solid-state decomposition. Widmanstätten FCC lamellae form from the allotriomorphic FCC precipitates at the B2 grain boundaries, leading to a lamellar microstructure, divided into two distinct sub-systems. Isothermal annealing further drives these individual sub-systems towards equilibrium via precipitation of ordered intermetallic phases. The transformation in FCC lamellae initiates by the formation of metastable L12 precipitates at shorter annealing times, which are eventually replaced by the equilibrium BCC and B2 phases, forming composite B2+BCC laths, on long term annealing. These results further exemplify that interesting transformation pathways lead to hierarchical microstructures within HEAs, and the fact that as processed conditions in these alloys are often far-from equilibrium. Graphical abstract: Image, graphical abstract